Hydrogen peroxide probes directed to different cellular compartments. - Mikalai Malinouski; You Zhou; Vsevolod V Belousov; Dolph L Hatfield; Vadim N Gladyshev (PLoS ONE, 2011)
Controlled generation and removal of hydrogen peroxide play important roles in cellular redox homeostasis and signaling. We used a hydrogen peroxide biosensor HyPer, targeted to different compartments, to examine these processes in mammalian cells.Reversible responses were observed to various redox perturbations and signaling events. HyPer expressed in HEK 293 cells was found to sense low micromolar levels of hydrogen peroxide. When targeted to various cellular compartments, HyPer occurred in the reduced state in the nucleus, cytosol, peroxisomes, mitochondrial intermembrane space and mitochondrial matrix, but low levels of the oxidized form of the biosensor were also observed in each of these compartments, consistent with a low peroxide tone in mammalian cells. In contrast, HyPer was mostly oxidized in the endoplasmic reticulum. Using this system, we characterized control of hydrogen peroxide in various cell systems, such as cells deficient in thioredoxin reductase, sulfhydryl oxidases or subjected to selenium deficiency. Generation of hydrogen peroxide could also be monitored in various compartments following signaling events.We found that HyPer can be used as a valuable tool to monitor hydrogen peroxide generated in different cellular compartments. The data also show that hydrogen peroxide generated in one compartment could translocate to other compartments. Our data provide information on compartmentalization, dynamics and homeostatic control of hydrogen peroxide in mammalian cells.